The role of short-chain fatty acids in immunity, inflammation and metabolism - Yao, Yao; Cai, Xiaoyu; Fei, Weidong; Ye, Yiqing; Zhao, Mengdan; Zheng, Caihong (Critical reviews in food science and nutrition, 2022)
Short-chain fatty acids (SCFAs) are carboxylic acids with carbon atom numbers less than 6, which are important metabolites of gut microbiome. Existing research shows that SCFAs play a vital role in the health and disease of the host. First, SCFAs are the key energy source for colon and ileum cells, and affect the intestinal epithelial barrier and defense functions by regulating related gene expression. Second, SCFAs regulate the function of innate immune cells to participate in the immune system, such as macrophages, neutrophils and dendritic cells. Third, SCFAs can also regulate the differentiation of T cells and B cells and the antigen-specific adaptive immunity mediated by them. Besides, SCFAs are raw materials for sugar and lipid synthesis, which provides a theoretical basis for studying the potential role of SCFAs in regulating energy homeostasis and metabolism. There are also studies showing that SCFAs inhibit tumor cell proliferation and promote apoptosis. In this article, we summarized in detail the role of SCFAs in immunity, inflammation and metabolism, and briefly introduced the role of SCFAs in tumor cell survival. It provides a systematic theoretical basis for the study of SCFAs as potential drugs to promote human health.